Hubungan Antara Kebiasaan Merokok Dengan Perjalanan Penyakit Rhinitis - Sabilarrusydi; Manuel Umbu Madiaha; Nimim Putri Zahara; Bambang Mulyawan (ARTERI : Jurnal Ilmu Kesehatan, 2023)
One of the rhinitis diseases is allergic rhinitis (RA) which is a condition of hypersensitivity of the nasal mucosa due to the appearance of Ig E characterized by symptoms of sneezing, itchy nose, runny nose and nasal congestion after exposure to allergens. Release of mediators gives rise to a fast phase response and a slow phase response. The habit of smoking is mostly carried out by people in the world and the number of smokers in Indonesia is ranked seventh in the world. This article was written using a systematic review model, by searching for articles from reputable journals, using the PUBMED search engine which then obtained 30 articles. Allergic rhinitis has a very complex pathophysiology, from the initial phase of the allergic response to the end. Many inflammatory cells, including macrophages, mast cells, B cells, T cells, eosinophils, and CD4+, sneak up on the lining of the nose after exposure to allergens. The cross-linking of IgE bound to mast cells by allergens, in turn, triggers the release of mediators, including leukotrienes and histamine which causes arteriolar dilation, increased vascular permeability, itching, mucus secretion, rhinorrhea, and smooth muscle contraction in the lungs. Increased total IgE levels and specific IgE levels can be caused by smoking status smoking. The severity of patients diagnosed with allergic rhinitis can be influenced by smoking habits or status. Smoking does not cause allergic rhinitis, but smoking makes allergic rhinitis symptoms worse.